Safflower productivity as related to soil water storage and management practices in semiarid regions - Quiroga, Alberto R. (2001)
In semiarid regions the availability of water has an important influence on dryland crop productivity. Water availability is closely related to soil organic matter (SOM) content, texture and soil thickness. Safflower (Carthamus tinctorius L.) is an important winter crop in some semiarid regions due to its deep roots and drought tolerance. However, its adaptation to different soil conditions is still not well known. The objective of this study was the evaluation of safflower productivity, in relation to soil properties, across 30 grower fields of the semiarid Pampas region of Argentina. The soils were Entic and Aridic Haplustolls under continuous row-cropping (CC) or pasture row crop rotations (PC). Grain yields varied between 0 and 1600 kg ha-1, and were positively correlated with the maximum soil water retention (SWR) of the top layer (0-20cm) and the soil use management (SUM, r=0.93, p < 0.01). Oil yield and plant growth was also positively correlated with SWR and SUM. This trend was explained on the basis of better water and nutrient supply to the plants in finer textured soils during the pronounced moisture deficiency that occurred at the flowering stage of the crop. In soils with similar textures, safflower production was highest in sites that included PC, had high SOM levels, and in which indurate sub-surface layers were absent. Highly productive dryland safflower crops in coarse textured soils from semiarid regions can be achieved by using cultural practices that increase SOM levels (pasture-arable crop rotation) and loosen compacted layers.